Effect of Temperature and Ph on Glucose Production Using Enzymatic Hydrolysis - Ahmad, Siti Solehah (2010)
Enzymatic hydrolysis is one of the effective methods in glucose production due to enzyme properties which are highly specific and very sensitive. Therefore, this paper was designed to study the effect of temperature and pH on glucose production using enzymatic hydrolysis. By using enzymatic hydrolysis, cellulase from Trichoderma reesei was used and supplemented with cellobiase from Aspergillus niger for increasing the glucose production. Cellulose as a substrate was hydrolyzed by these enzymes to produce glucose and the amount of glucose production was determined by high-performance liquid chromatography (HPLC). The result showed that the highest glucose concentration was produced at the temperature of 50°C and pH 5.0 while the lowest glucose production was produced at 30°C and pH 6.5 which were 21.09 mg/ml and 3.55 mg/ml, respectively. By changes the temperature and pH above or below 50°C and pH 5.0 results in low glucose production because the enzyme was lose their three-dimensional functional shape due to disruption from unstable condition of the environment system. As a conclusion, all the requirement for complementary in the configuration of cellulose and enzyme must be considered seriously for the highest glucose production.